Optimization of Diagnostic Criteria for Necrotisius Fasciitis in Diabetes Mellitus (Texas Journal of Medical Science, 2023)
The concept of relevance holds significance in various academic disciplines. It refers to the degree to which The clinical presentation of necrotizing fasciitis (NF) has been documented in historical records dating back to 1871, when it was first described by Joseph Jones, an American military physician, under the term "hospital gangrene." In the year 1924, Meleney made the discovery that the etiological agent responsible for this particular pathological condition is hemolytic streptococcus. The condition was classified as hemolytic streptococcal gangrene. However, in 1972, B. Wilson introduced a significant diagnostic indicator known as fascial necrosis. Hence, the widely acknowledged definition of necrotizing fasciitis, as proposed by B. Wilson, has been established